The influence of multilateral development institutions on Latin American development strategies (2016)
This paper discusses the changing relation between Multilateral Development Institutions and Latin America, especially since the 1980s to the present. The paper first depicts how MDI's influence on LA has varied over time and across countries, depending on access to international private capital markets, the development of long-term markets for domestic currency government bonds, and the significant reduction of macro-financial vulnerabilities in the region. It then illustrates how MDI's views on macroeconomic and development policies has evolved over time, influenced by academic developments and also by Latin American governments. Finally, the paper shows how most governments in the region, whether left-wing or center-right oriented, have increasingly converged with MDI's recommendations on macro-financial policies, while historically many, from all ends of the political spectrum, applied both macro and micro policies differing with MDI's views.